2017
DOI: 10.1002/advs.201700048
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrrole‐Based Conjugated Polymer Entailing Triethylene Glycols as Side Chains with High Thin‐Film Charge Mobility without Post‐Treatments

Abstract: Side chain engineering of conjugated donor–acceptor polymers is a new way to manipulate their optoelectronic properties. Two new diketopyrrolopyrrole (DPP)‐terthiophene‐based conjugated polymers PDPP3T‐1 and PDPP3T‐2, with both hydrophilic triethylene glycol (TEG) and hydrophobic alkyl chains, are reported. It is demonstrated that the incorporation of TEG chains has a significant effect on the interchain packing and thin‐film morphology with noticeable effect on charge transport. Polymer chains of PDPP3T‐1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…[7,16] In order to overcome these challenges, more recent work has shown that the incorporation of ionic or ethylene glycol based sidechains onto the backbone of the CP can promote ionic conductivity, [22,23] although the performance has been shown to be very sensitive to relative percentage of hydrophobic/hydrophilic groups on the backbone. [24] The addition of ethylene glycol chains to CPs has also been shown to promote closer π-stacking of conjugated backbones, [25,26] enhance the dielectric constant, [27,28] and afford higher charge carrier mobility in transistor devices [29,30] compared to the analogous alkylated polymers.…”
mentioning
confidence: 99%
“…[7,16] In order to overcome these challenges, more recent work has shown that the incorporation of ionic or ethylene glycol based sidechains onto the backbone of the CP can promote ionic conductivity, [22,23] although the performance has been shown to be very sensitive to relative percentage of hydrophobic/hydrophilic groups on the backbone. [24] The addition of ethylene glycol chains to CPs has also been shown to promote closer π-stacking of conjugated backbones, [25,26] enhance the dielectric constant, [27,28] and afford higher charge carrier mobility in transistor devices [29,30] compared to the analogous alkylated polymers.…”
mentioning
confidence: 99%
“…Experimentally, precisely controlling the RDOC for CP is not straightforward. In general, the conventional DSC is not capable to quench the CPs to the supercooled, or completely amorphous state owing to the fast crystallization rate of CPs . For example, as shown in Figure S7, the crystallization of P3(2EB)T is inevitable upon cooling it from its melt state with conventional DSC even at 100 K min −1 , while faster cooling speed using flash DSC can trap P3(2EB)T into the fully amorphous phase using a cooling rate of 60,000 K min −1 (1,000 K s −1 ), as shown in Figure subsequently.…”
Section: Resultsmentioning
confidence: 99%
“…( T g discussed herein refers to backbone T g .) For example, it has been shown that for diketopyrrolopyrrole‐based (DPP) polymers, neither conventional DSC nor Flash DSC exhibits a clear T g …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the interaction between dielectric and semiconductor layer is widely addressed through the appropriate choices of the SAM material, and its effective treatment on the dielectric surface before the semiconductor material is deposited on top of dielectric surface 20 . Among many possible silanes based SAM treatments on the SiO 2 surface, octyl trichlorosilane (OTS) is one of the most widely used 21 23 due to its appropriate alkyl chain length which enhances alkyl–alkyl interdigitation between the SAM alkyl chain and alkyl chain substituted on the conjugated backbone motifs.…”
Section: Introductionmentioning
confidence: 99%